Buddhist-Muslim Relations in a Theravada World - Frydenlund, Iselin (Palgrave Macmillan US, 2020)
Intro -- Foreword -- Acknowledgements -- Contents -- Notes on Contributors -- List of Figures -- Chapter 1 An Introduction: Buddhist-Muslim Relations in a Theravada World -- Aims of This Volume -- The Historical Legacy of Muslim-Buddhist Relations -- Muslim-Buddhist Relations in Pre-colonial South and Southeast Asia -- European Colonialism and the Rise of Modern Nationalism -- Contemporary Issues -- Reflections on the Study of Buddhist-Muslim Relations -- Volume Overview -- References -- Part I Historical Country Overviews -- Chapter 2 Historical Threads of Buddhist-Muslim Relations in Sri Lanka -- Tamil-Speaking Muslims -- Robe and Plough … and Trader -- Caste and Ethnicity -- A Myth of a Trader Deity -- Muslim Pirates in the Kotte Period -- Western European Christianity: Intolerance and the State -- Plantation Capitalism -- Grain Riots and 1915 -- Closed and Open Economies and Their Changing Global Articulations -- Conclusion -- References -- Chapter 3 Buddhist-Muslim Interactions in Burma/Myanmar -- Muslim and Buddhist Identities and Practices in Myanmar -- The Language and Practices of Othering -- Historical Overview -- Precolonial Period (Ninth Century-1826) -- Colonial Period (1826-1948) -- Post-independence Parliamentary Period (1948-1962) -- Military Rule and After (1962-Present) -- Conclusion -- References -- Chapter 4 Buddhist-Muslim Dynamics in Siam/Thailand -- Buddhist-Muslim Interactions Past and Present -- The Thai State and Its Expansion -- Indic and Buddhist Influences in South Thailand -- Muslims in Central Thailand During the Ayutthaya Period (1351-1767) -- Managing the Radial Polity -- Muslims in South Thailand Since the Bangkok Period -- Muslims in Central Thailand After the Bangkok Period -- Descendants of Malay Muslims in Central Thailand -- Muslims of North Thailand -- Thai Muslim Identity in Central and North Thailand.